Enhancing Stroke Recovery Across the Life Span With Noninvasive Neurostimulation. Issue 2 (March 2020) - Dukelow, Sean; Kirton, Adam
Abstract : Summary: Stroke is the leading cause of neurologic disability not only in adults but perinatal and childhood stroke affect millions of children as well worldwide with deficits that last a lifetime. The rapidly increasing evidence base for how noninvasive neuromodulation may enhance stroke recovery in adults may be applicable to the youngest stroke survivors. In return, how the plasticity of the developing brain contributes to stroke recovery and its modulation may provide equally valuable insight toward mechanisms and opportunities for enhancing recovery in all stroke patients. Despite this synergistic relationship, examinations of stroke recovery and neuromodulation across the life span have rarely been considered. Here, we attempt to amalgamate the worlds of adult, childhood, and perinatal stroke to explore the differences and commonalities between the models and approaches that are driving advances in noninvasive neuromodulation toward better outcomes for stroke patients of all ages.